2004
DOI: 10.1007/s00277-003-0731-0
|View full text |Cite
|
Sign up to set email alerts
|

TNF-? induces changes in LDH isotype profile following triggering of apoptosis in PBL of non-Hodgkin?s lymphomas

Abstract: Based on the possibility of tumor necrosis factor (TNF)-alpha to perform multiple and opposite biologic effects, we simultaneously investigated in vitro its effects on intracellular lactate dehydrogenase (LDH)-H and LDH-M isoenzyme activity and morphological characteristics following induction of apoptosis in peripheral blood mononuclear cells (PBMC) of non-Hodgkin's lymphoma patients (NHL) prior to and after the end of applied chemotherapy. TNF-alpha showed a significant increase ( p<0.05) of LDH-H and LDH-M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…The overall description of the differentiating treatments was outlined in Figure , together with some characteristics acquired by the cells and relevant for the discussion of the results (i.e., growth rate, cardiac markers, mitochondrial mass, and mitochondrial F 1 F O ATP synthase assembly). During the treatment, cytotoxicity was verified by a sensitive LDH‐release assay, as widely reported for several cell systems [Jurisic, ; Jurisic et al, ]. Very low treatment cytotoxicity was observed (Fig.…”
Section: Resultssupporting
confidence: 57%
“…The overall description of the differentiating treatments was outlined in Figure , together with some characteristics acquired by the cells and relevant for the discussion of the results (i.e., growth rate, cardiac markers, mitochondrial mass, and mitochondrial F 1 F O ATP synthase assembly). During the treatment, cytotoxicity was verified by a sensitive LDH‐release assay, as widely reported for several cell systems [Jurisic, ; Jurisic et al, ]. Very low treatment cytotoxicity was observed (Fig.…”
Section: Resultssupporting
confidence: 57%
“…We previously reported that patients with multiple myeloma have stage dependent increase of serum TNF-a that strongly correlated with tumor burden, percentage of plasma cell infiltration in bone marrow and presence of osteolyses [16]. TNF-a can modulate NK cell activity by inducing disturbance in cell metabolic activity following induction of apoptosis and necrosis, depending on TNF receptor system expression [17][18][19][20]. We show here, like in other patients with solid tumors (breast cancer and malignant melanoma) as well as in hematological diseases (Hodgkin's and non-Hodgkin's lymphoma) that multiple myeloma patient's show impairment of NK cell activity [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…45 In tumor cells the rate of apoptosis is accompanied by the increase in LDH-B and correlates with cisplatin 46 and TNF-alpha sensitivity. 47 Although the physiological role of annexins is still unclear, they have been shown to be involved in membrane trafficking, fusion and permeabilization. 48 CLIC1 expression in cultured CHO-K1 cells stimulates chloride channel activity in plasma and nuclear membranes.…”
Section: Discussionmentioning
confidence: 99%